2001
DOI: 10.1037/0021-843x.110.2.309
|View full text |Cite
|
Sign up to set email alerts
|

Coping dimensions, life stress, and adolescent substance use: A latent growth analysis.

Abstract: The relation of seven coping dimensions to substance (tobacco, alcohol, marijuana) use was tested with a sample of 1,668 participants assessed at mean age 12.5 years and two yearly follow-ups. An associative latent-growth model showed one index of engagement (behavioral coping) to be inversely related to initial level of adolescent use and growth over time in peer use. Three indices of disengagement (anger coping, helpless coping, and hangout coping) were positively related to initial levels of peer use and ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
161
2
2

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 211 publications
(179 citation statements)
references
References 63 publications
14
161
2
2
Order By: Relevance
“…It is possible that adolescents may have engaged in health risk behavior as a temporary escape from stressful aspects of violence involvement. Previous research shows that violent victimization and perpetration are both linked with adjustment problems [24][25][26] and that some individuals are motivated to engage in substance use [9,[14][15][16][17] and sexual behavior [9,[16][17] as a means of coping with stressful life circumstances. Further research is needed to demonstrate whether longitudinal associations between violence involvement and other forms of health risk behavior are mediated by cognitive and affective responses to violence, including motivations to engage in risk behavior as a means of coping with violence.…”
Section: Stress-response Frameworkmentioning
confidence: 99%
See 3 more Smart Citations
“…It is possible that adolescents may have engaged in health risk behavior as a temporary escape from stressful aspects of violence involvement. Previous research shows that violent victimization and perpetration are both linked with adjustment problems [24][25][26] and that some individuals are motivated to engage in substance use [9,[14][15][16][17] and sexual behavior [9,[16][17] as a means of coping with stressful life circumstances. Further research is needed to demonstrate whether longitudinal associations between violence involvement and other forms of health risk behavior are mediated by cognitive and affective responses to violence, including motivations to engage in risk behavior as a means of coping with violence.…”
Section: Stress-response Frameworkmentioning
confidence: 99%
“…Longitudinal associations would suggest additional mechanisms. For example, violence involvement may lead to increases in substance use and sexual behavior over time if engagement in health risk behavior is a means of distracting oneself from or coping with stressful aspects of violence (i.e., stress-response framework [9,[14][15][16][17]). Engagement in substance use and sexual activity with multiple partners may lead to increases in violence involvement over time if these health risk behaviors place adolescents in situations in which violence is more likely to occur (i.e., vulnerability to violence framework [18][19][20]).…”
Section: A Longitudinal Perspectivementioning
confidence: 99%
See 2 more Smart Citations
“…The relationship between stress and substance use is well established (Cooper, Wood, Orcutt, & Albino, 2003;Dugan et al, 1999;Wagner et al, 1999;Wills, Sandy, Yaeger, Cleary, & Shinar, 2001). Hussong and Chassin (2004) reported that young adult alcohol use, but not drug use, was crosssectionally related to an interaction between avoidant coping and young adult transition-related stress.…”
Section: Stress As a Moderatormentioning
confidence: 99%